Sistem Rekomendasi Dosen Pembimbing Skripsi Berdasarkan Kompetensi Menggunakan Metode Scrum dengan Algoritma Sequential Searching Berbasis Mobile - Edo Pratama; Isnandar Agus; Rio Kurniawan (TEKNIKA, 2023)
The development of incresingly sophisticated information technology has presented various applications that users can use to complete their tasks. This study aims to design and build a competency-based thesis supervisor recommendation system software.The software development method used is the scrum method; this is done to predict and see any errors that arise during the initial development of the application. The Scrum method includes the Product backlog, Sprint backlog and Increment using the Sequential searching algorithm for pseudocode.The results of this study are the recommendation system software for thesis supervisors. This system makes it easier for students doing their thesis to get supervisors according to the lecturer's specialization and expertise. This system can display student data, specializations, lecturer research and lecturer recommendations for thesis supervisors. Keywords: Application, Scrum method